2016
DOI: 10.1590/1807-3107bor-2016.vol30.0137
|View full text |Cite
|
Sign up to set email alerts
|

The effect of standardised implantoplasty protocol on titanium surface roughness: an in-vitro study

Abstract: The effect of standardised implantoplasty protocol on titanium surface roughness: an in-vitro study Abstract: To analyse the changes of surface characteristics of machined and moderately roughened titanium disks following a standardised implantoplasty protocol. Forty titanium discs (machined: n = 20; moderately roughened: n = 20) were instrumented with one half of each disc maintained as the control (non-instrumented). The standardised implantoplasty protocol was carried out using a custom jig with the sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Bollen et al suggested that bacterial colonization is not affected as long as the substrate roughness is below Ra 0.2 μm [28]. In the present study only the POL control group had a S a value below this threshold, which is in agreement with previous studies [9,10,13]. To the best of the authors' knowledge, only Costa-Berengeuer and co-workers have reported S a values of less than 0.2 μm by the use of mere chairside bur-sequences [16].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Bollen et al suggested that bacterial colonization is not affected as long as the substrate roughness is below Ra 0.2 μm [28]. In the present study only the POL control group had a S a value below this threshold, which is in agreement with previous studies [9,10,13]. To the best of the authors' knowledge, only Costa-Berengeuer and co-workers have reported S a values of less than 0.2 μm by the use of mere chairside bur-sequences [16].…”
Section: Discussionsupporting
confidence: 93%
“…Implantoplasty is above all performed to counter microbial challenges, and its impact on preventing bacterial recolonization and facilitating removal of bacterial colonization is considered pivotal to healing and homeostasis of peri-implant health following implantoplasty treatment in response to peri-implantitis challenges. So far in vitro studies on implantoplasty have focused on surface roughness [8][9][10], heat generation [11][12][13], and fracture resistance [14,16,17]. This study provides some new insights on the soft tissue component following experimental implantoplasty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…() obtained a mean R a value of 0.32 ± 0.14 μm after conducting a five bur implantoplasty procedure (diamond burs 106‐, 40‐, 15‐μm grit, plus Brownie ® and Greenie ® silicone‐impregnated polishers), which took a mean time of 21 ± 4 min per implant. Furthermore, three studies have reported R a values of > 4.0 μm after standardized implantoplasty on titanium disks (Tawse‐Smith, Kota, Jayaweera, Vuuren & Ma, ; Tawse‐Smith et al., ) and titanium dental implants (de Souza Junior et al., ). In the three latter studies, the final surface was significantly rougher than the original one.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reported working time with each bur (less than 1 min), the type and shape of the burs, bur angulation, and area and shape of the treated surfaces are factors that might explain the disparity in their results. Indeed, the outcomes of studies that use titanium disks (Tawse‐Smith et al., , ) are difficult to generalize to a clinical situation because of the absence of threads.…”
Section: Discussionmentioning
confidence: 99%